0142 The Cumulative Effect of Partial Chronic Sleep Restriction on the Neural Processing Stream in Neurologically Normal Individuals. (12th April 2019) - Gossard, Thomas R; Westerland, Sarah M; Linn-Evans, Maria; Timm, Paul C; Sandness, David J; Dueffert, Lucas; Feemster, John C; McCarter, Stuart J; Teigen, Luke; Covassin, Naima; Svatikova, Anna; Ruzek, Lucas; et al.
Abstract: Introduction: Event-related potentials (ERP) are averaged electroencephalogram (EEG) responses to stimuli enabling precise temporal characterization of neural processing. We analyzed the temporal evolution and course of cognitive processing impairments during a 16 day randomized, cross-over sleep restriction experiment, by analyzing visual attention (N2pc), stimulus classification (P3), and decision making (error-related negativity (ERN) and positivity (Pe)) ERPs. Methods: Eighteen healthy subjects (8 women, 10 men; age 22.8±4.88, range 18-36 years underwent sleep restriction (3 acclimation nights of 9 hours of time in bed, then 9 experimental 4 hours nights, then 3 recovery sleep nights), and control sleep (15 nights at 9 hours of time in bed) sequences in random order. EEG recordings during a visual attention task were completed once (day 3) during the acclimation period, 3 times during the experimental period (days 5, 6, 9), and once in the recovery period (day 15). Post-hoc off-line ERP data processing yielded N2pc, P3, and ERN/Pe waveforms with comparison of primary amplitude and latency measures across experimental timepoints utilizing mixed linear regression modeling. Results: ERN and Pe amplitudes were significantly reduced during sleep restricted days 6 and 9 (both p<0.05, for Pe p<0.02), and P3 amplitude was significantly lower during sleep restricted days 9 and 15 (both p<0.02), compared to corresponding control sequence days. Pe (day 6) and P3 (days 5, 6, 9) fractional area latencies were also significantly delayed during sleep restriction compared to the corresponding control sequence days (both p<0.03). There were no significant N2pc amplitude or latency differences between conditions. Conclusion: These data suggest that stimulus classification and error-monitoring, reflecting mesial temporal and frontal neuronal network processing, are selectively impaired during chronic sleep restriction. Covert attentional shifting remained intact, implying greater allocation of top-down executive resources toward preserving attentional capacity at the cost of degraded error monitoring capacities during sleep restriction. Further research analyzing sleep homeostatic drive and vigilance is planned to determine whether these brain functions influence visual processing efficiency. Support (If Any): NIH/NHLBI R01 HL 114676; Mayo Clinic CCaTS 1 UL1 RR024150-01